Strengthening decision-making processes to promote water sustainability in the South African mining context: the role of good environmental governance and the law - Kengni, Bernard (University of Cape Town, 2020)
This thesis examines whether the concept of good (environmental) governance provides a useful tool and legal base for the achievement of water sustainability in South Africa's mining sector. The thesis introduces water pollution as one sustainability challenge that South Africa is facing in its mining sector. The main question is how the legal framework should promote and guide water sustainability through good environmental governance. The question results from the fact that mining is a constant threat to water resources. Mining is one of the leading causes of water pollution which adversely affects human life among others when water contaminated with heavy metals is consumed. Farming, as an essential component of food security, is under constant threat in places like Mpumalanga as soils are rendered less productive by mine-contaminated water infiltrating from topsoil or rising from underground mines. Similarly, polluted water adversely affects biodiversity, thus, destroying ecosystems and vegetation which serve as livestock feed. The analysis of sustainability, governance and good governance theories and specific concepts underpinning them shows that they can inform water protection in the South African mining sector. Sustainability, found to be a broad and interdisciplinary concept, is a necessary guideline for the pursuit of water governance in the mining sector. Despite conflicting perceptions or facts regarding sustainability, it is evident that for water to be preserved, sustainable practices are essential. This requires mining activities to be conducted while always minimising the occurrence of water pollution to ensure water sustainability in the South African mining sector. The thesis also expounds that water sustainability pursued through governance practices is likely to be effective in alleviating or preventing water concerns. Thus, the concept of governance is presented as a tool with which individuals or organisations can achieve effective water sustainability, through decision-making, planning and law enforcement. Governance as a concept is complex, multifaceted and interdisciplinary, but can ensure water sustainability and the wellbeing of members of society who depend on the natural environment. The thesis further highlights that water sustainability is more likely when pursued through governance in its best possible form. The concept of good environmental governance is therefore explained as a theory that can guide effective decisionmaking and serve as a tool at the disposal of interested and affected parties to judge the performance of administrative officials. Effective decision-making processes and its elements are to be promoted through cooperative governance, accountability, transparency and public participation, for effective administrative action. The thesis then analyses the South African legal framework and establishes that water governance in the mining sector is extensively catered for therein. The Constitution sets the water sustainability mandate based on which legislation is enacted, both followed by legal interpretation in the courts. The analysis, however, show that there are various shortcomings relating to the implementation and enforcement of the law through administrative action. Nevertheless, the analysis remains hopeful that water sustainability can still be achieved in the mining sector. Despite the existence of environmental provisions and various attempts to achieve water sustainability, the current South African legal framework still fails to control water pollution effectively. The failure may be attributed to the shortcomings of the said framework, but it is, to a larger extent, a result of poor implementation and enforcement. One main reason is less effective administrative action due to inefficient decision-making processes, which implies that the quality of governance regarding water protection in the mining sector is inadequate. Such findings show that water sustainability could have been achieved or improved if decisionmakers had relied fully on good governance principles to implement and enforce provisions aimed at water protection in the mining sector. Hence, this thesis finds that no new regulation is required; rather it suggests a reform of various provisions within the existing legal framework to improve water sustainability. This is subject to improved implementation and enforcement mechanisms.